Visual search pattern during free viewing of horizontally flipped images in patients with unilateral spatial neglect. (April 2019) - Ohmatsu, Satoko; Takamura, Yusaku; Fujii, Shintaro; Tanaka, Kohei; Morioka, Shu; Kawashima, Noritaka
Abstract: Eye tracking is an effective tool for identifying behavioural aspects of unilateral spatial neglect (USN), which is a common neurological syndrome that develops after a right hemisphere lesion. Here, we attempted to elucidate how the neglect symptom affects the symmetry of the gaze pattern, by performing an analysis of gaze distribution during the free viewing of a pair of horizontally flipped images. Based on their Behavioural Inattention Test (BIT) scores, 41 patients with right-hemisphere damage were classified into those with USN (n = 27) and those without USN (right hemisphere damaged - RHD; n = 14). Eye movement was recorded while the patients viewed six pairs of horizontally flipped images on a computer display. A pair of flipped images has both similar and consistent elements, as well as a reversed spatial location of objects (right-left). We calculated the gaze distribution, extent of gaze shift, total gaze distance, and gaze velocity in each direction. Our results demonstrated a significantly larger rightward gaze shift in the USN group, which showed a significant correlation with the BIT score. More importantly, the extent of gaze shift and total gaze distance were similarly modulated by the contents of the displayed images in both the USN and RHD groups. Our findings suggest that analyses of gaze distribution during the free viewing of a pair of horizontally flipped images have the potential to precisely reveal neglect behaviour, and our results provide important implications for rehabilitation.